The role of sustainable marketing in achieving competitive advantage through Customer perceived value - AL-shammari , Abeer M. Mahdi; Al-BakrI, Fatima Hussein Kazem (The journal of contemporary issues in business and government, 2023)
The current research was concerned with studying the nature of the relationship and the influence between three variables represented by (sustainable marketing, Customer perceived value, and the competitive advantage). Of the hospital workers within the work departments in it, and the nature of the answers was analyzed statistically through the spss statistical program to get to the fact of accepting or rejecting the four hypotheses of the research, which are the hypotheses of correlation and influence relationships, and through the statistical results, the second hypothesis was accepted and the rest of the hypotheses were rejected based on the level Statistical significance. The research reached a set of recommendations that support the application of the concept of sustainable marketing in the hospital enhancing the competitive advantage by intensifying courses and continuous training, as well as the real participation of workers in formulating marketing strategies, supporting services provided to customers, listening carefully to the problems experienced by workers or addressing poor quality of services, and paying attention to environmental responsibility.